Legacy Effect of Long-Term Elevated CO2 and Warming on Soil Properties Controls Soil Organic Matter Decomposition - Jie Li; Baobao Sun; Cheng Liu; Marios Drosos; Xuhui Zhang; Xiaoyu Liu; Lianqing Li; Genxing Pan (Agriculture, 2023)
Plant litter quality is one of the key factors that control soil organic matter (SOM) decomposition. Under climate change, although significant change in litter quality has been intensively reported, the effect of litter quality change on SOM decomposition is poorly understood. This limits our ability to model the dynamics of soil carbon under climate change. To determine the effect of litter quality and soil property change on SOM decomposition, we performed a controlled, reciprocal transplant and litter decomposition experiments. The soils and plant litters were collected from a long-term field experiment, where four treatments were designed, including: (1) the control without warming at ambient CO2; (2) elevated atmospheric CO2 up to 500 ppm (C); (3) warming plant canopy by 2 °C (T); (4) elevated CO2 plus warming (CT). We found that elevated CO2 and warming altered the litter quality significantly in terms of macronutrients’ content and their stoichiometry. Elevated CO2 decreased the concentration of N in rice and wheat straw, while warming decreased the concentration of N and K in wheat straw. However, the change in plant litter quality did not lead to a shift in SOM decomposition. On the contrary, the legacy effect of long-term elevated CO2 and warming on soil properties dominated the decomposition rate of SOM. Elevated atmospheric CO2 suppressed SOM decomposition mainly by increasing phosphorous availability and lowering the soil C/N, fungi/bacteria ratio, and N-acetyl-glucosaminidase activity, while warming or elevated CO2 plus warming had no effect on SOM decomposition. Our results demonstrated that the changes in soil property other than litter quality control the decomposition of SOM under climate change, and soil property change in respond to climate change should be considered in model developing to predict terrestrial soil carbon dynamics under elevated atmospheric CO2 and warming.